Peningkatan Hasil Belajar matematika dengan Model Kooperatif Type STAD Materi Sifat-Sifat Bangun Datar Pada Siswa Kelas V SDN 004 Rambah Hilir - Basri T (STKIP Rokania Pasir Pangaraian, 2018)
This study aims to improve the learning outcomes of Mathematics with Model Cooperative Type STAD Material Properties Build Data On Students Class V SDN 004 Rambah Hilir. Sand Rokan Hulu Pengaraian District. The subjects of this study are the students of class V which amounted to 21 people consisting of 14 men and 7 women. The collection in this study using the method of test and observation. Parameters measured are Student Outcomes Includes Absorption Ability And Completed Learning Obtained From Post Test and Deuteronomy, Student Learning Activity And Teacher Activity. The results showed that the use of STAD type cooperative model can improve Mathematical learning outcomes. At prasiklus the result of daily test is the average score 58,8. The average daily repeat value of cycle I is 73.6 and the average in cycle II is 78.8. It shows an increase in value from prasiklus to cycle II of 20.0. Completed Learning of New Students Achieved Classically in Cycle II, ie 90.5%. Student Activity, Both Listening and Noting Activity Master's Comment, Working on Lks and Presentations, Questions and Answers Activity Questions Average 76.2 in cycle I increased to 881 in cycle II. Teacher Activity Also Experienced Increased Cycle I average of 85 with Category Good Once, Cycle II average 95.